Errors of Omission: Missed Nursing Care - Kalisch, Beatrice J; Xie, Boqin (Western journal of nursing research, 2014)
A series of studies on missed nursing care (i.e., required standard nursing care that is not completed) is summarized. Missed nursing care is substantial and similar levels are found across hospitals. Reasons for missed nursing care are staffing resources, material resources, and communication and these are also similar across hospitals. The higher the staffing levels, the fewer occurrences of missed nursing care. Magnet status and higher levels of teamwork are associated with less missed nursing care, and more missed care leads to a lower level of staff satisfaction. Missed nursing care has been found to be a mediator between staffing levels and patient falls. Patient identified missed nursing care predicts adverse events (i.e., falls, pressure ulcers, new infections etc.).